Biochemical changes in groundnut pods due to infestation of bruchid Caryedon serratus (Olivier) under stored conditions. (September 2020) - Sreedhar, M.; Singh, D.V.; Reddy, D.V. Chandrasekhar; Vasudha, A.
Abstract: A study on the "Biochemical changes in groundnut pods due to infestation of bruchid, Caryedon serratus (Olivier) under stored conditions" was conducted at Department of Entomology, College of Agriculture, SVPUA&T, Meerut during August 2018 to February 2019. Results of the study showed that there was significant increase in weight loss of the groundnut pods (test varieties) with the increase in storage period i.e. 30, 90, and 150 DAS (days after storage). This significant increase in weight loss was due to infestation of groundnut bruchid. In addition to the weight loss, distinct differences in the biochemical components such as sugars, proteins, tannins, phenols were found in between infested and uninfested groundnut pods. A significant reduction in sugars, tannins, phenol whereas increase in protein content was noticed with the increase in the storage period i.e. 30, 90 and 150 DAS. Correlation studies relating weight loss and biochemical components from different groundnut varieties (resistant and susceptible) due to bruchid infestation were also worked out in the study. Pod sugar and pod protein content showed significant positive correlation with weight loss (positive effect on the development of the bruchid). While, pod tannins and pod phenols content showed significant negative correlation with weight loss (exerted a negative effect on the development of the bruchid). Highlights: Biochemical changes in groundnut pods due to infestation of bruchid under stored conditions. Increasing in weight loss of the groundnut pods with the increase in storage period. Biochemical contents there was a significant reduction in sugars, tannins, phenol and increase in protein content. Pod sugars and pod protein showed significant positive correlation with weight loss. Pod tannins and pod phenols showed significant negative correlation with weight loss.